Design of a passive radiative and evaporative cooling mortar coating that achieves sub-ambient temperature in tropical daytime. - Chionh, Daryl Zhenyu (Nanyang Technological University, 2023)
Cooling is a large component of energy usage in buildings, especially in tropical climates such as Singapore. Improving the energy efficiency of buildings through passive cooling is thus a very enticing prospect, especially given the emphasis placed on energy efficiency and green buildings in the Singapore Green Plan. The 2 ways of passive cooling discussed in this paper are radiative and evaporative cooling. Passive radiative cooling has been proven to independently achieve good cooling performances in temperate climates. However, in tropical climates which have high solar irradiance and humidity, it has not been successful in achieving sub-ambient temperatures especially during high solar conditions such as noon to mid noon periods. Evaporative cooling has also been proven to achieve some cooling performance, and this project thus intends to utilise it in conjunction with radiative cooling to achieve sub-ambient temperature cooling in tropical climates under high solar conditions for the first time. The use of both cooling mechanisms in a building exterior coating has the potential to revolutionise cooling and consequently energy efficiency in the building industry. Herein, we document the design of a prototype paste that demonstrates good passive cooling performance, with adequate mechanical properties for application as a coating onto the exteriors of buildings. The resultant paste demonstrated a solar reflectance of 90.5%, infrared emittance of 93% within the 8-13μm atmospheric window, and sustained daylight sub-ambient temperatures of more than 2°C below ambient temperatures during peak solar irradiation conditions.